PENGEMBANGAN ALAT SKRINING UNTUK HIPERTENSI - Heryudarini Harahap; Yekti Widodo; Sri Muljati; Agus Triwinarto; Imam Effendi (GIZI INDONESIA, 2010)
THE DEVELOPMENT OF SCREENING TOOL FOR HYPERTENSIONThe increasing prevalence of hypertension is an important public health problem contributing to significant excess disease and mortality. The risk factors of high blood pressure were smoking, sex, age, consumption, activity, obesity, and heredity. Studies showed that subjects didn’t aware about their blood pressure as well as subjects’ knowledge about risk and symptom of hypertension was not good. Hypertension prevention can be done by giving screening tools to detect the blood pressure as well asgiving information about risk and symptom of hypertension. The objective of the study was to develop screening tool to detect hypertension. A cross-sectional survey was conducted in Bogor, North Jakarta and Tangerang district. Blood pressure was collected using spyhgmanometer. The JNC 7 was used to classify of hypertension. Screening tool and leaflet was developed based on the result of Basic Health Research data set as well as literature study. The study had three activities that were focus group discussion, validity and reliability, as well as screening tool trial. Results: Validity test showed that over 17 questions only 6 questions were valid (p0,05, r = 0,176). After re-construction of screening tool questions then validity test was done again. Over 15 questions, 12 was valid (p0,05, r = 0,07).Eventhough 3 questions were not valid that questions were still included in that screening tools. Reliabilty of screening tool was realiable (α Cronbach’s = 0.586). The sensitivity (Se) and Specificity (Sp) of subjects that had been have 7 scores or higher was had Se 61.6 and 64.1 Sp respectively. Conclusion: This study implies that hypertension screening tool can be used as screening tool to detect hypertension.Keywords: hypertension, obesity, sensitivity, screening tool, specificity